An Application of the Shift Share Analysis for Transformation of the Agricultural Sector in Economic Areas at South East Sulawesi - Abidin, Zainal - (Informatika Pertanian, 2015)
Agriculture sector is still dominan in Product Domestic Regional Bruto (PDRB) at South East Sulawesi Province. Shift share Analysis is one of analysis tools that can be used to analyze shift and share of overall of sectors of PDRB. The research was conduted to identify shifting overall sectors of PDRB of South East Sulawesi with shift-share analysis. The research used GDP of Indonesia, PDRB of South East Sulawesi and PDRB of cities/regenceis in South East Sulawesi 2003 and 2013 year base on constant price at year 2000. The result of research showed that application of shift share analysis can give overview about agriculture transformation in South East Sulawesi. Developing agricultural sector in South East Sulawesi depends on national development. The growth of agricultural sector in South East Sulawesi is classified as slow, and have Net Shift (NS) around IDR 144.868,720 million. Agricultural sector also has competitive advantage, specialization and also allocation effect. Shift share analysis also showed that agricultural sector has strong linkage with other sectors and has positif influence with other sectors to push regional output. This analysis needs to be applicated at micro levels to get agricultural commodities transformation that has competitive advantage and specialized to develop for increasing regional output in South East Sulawesi.